Awareness and Completion of Advance Directives Among Korean American Older Adults - Dobbs, Debra (J Am Geriatr Soc, 2015)
There has been growing concerns about racial and ethnic disparities in completion rates of advance directives (ADs) among community-dwelling older populations. While differences in AD completion rates in non-Hispanic Whites and African Americans have been reported, not much is known about the awareness and completion of ADs in other groups of ethnic minorities. Using a sample of community-dwelling Korean American older adults (n = 675) as a target, factors associated with their awareness and completion of ADs were explored. Guided by Andersen's behavioral health model, predisposing (age, sex, marital status, and education), need (chronic conditions and functional disability), and enabling variables (health insurance and acculturation) were included in the separate logistic regression models of AD awareness and AD completion. In both models, acculturation was found to be a significant predictor; those who had a higher level of acculturation were more likely to be aware of ADs and to have completed ADs. This study contributes to the knowledge about the role of acculturation in explaining AD awareness and completion among Korean American older adults and provides practice implications for possible AD educational interventions for this older adult minority population.